Semipurified ethyl acetate partition of methanolic extract of Melastoma malabathricum leaves exerts gastroprotective activity partly via its antioxidant-antisecretory-anti-inflammatory action and synergistic action of several flavonoid-based compounds - Ismail Suhaimy, Noor Wahida; Noor Azmi, Ahmad Khusairi; Mohtarrudin, Norhafizah; Omar, Maizatul Hasyima; Md Tohid, Siti Farah; Cheema, Manraj Singh; Teh, Lay Kek; Salleh, Mohd Zaki; Zakaria, Zainul Amiruddin (Hindawi Publishing Corporation, 2017)
Recent study has demonstrated the gastroprotective activity of crude methanolic extract of M. malabathricum leaves. The present study evaluated the gastroprotective potential of semipurified extracts (partitions): petroleum ether, ethyl acetate (EAMM), and aqueous obtained from the methanolic extract followed by the elucidation of the gastroprotective mechanisms of the most effective partition. Using the ethanol-induced gastric ulcer assay, all partitions exerted significant gastroprotection, with EAMM being the most effective partition. EAMM significantly (i) reduced the volume and acidity (free and total) while increasing the pH of gastric juice and enhanced the gastric wall mucus secretion when assessed using the pylorus ligation assay, (ii) increased the enzymatic and nonenzymatic antioxidant activity of the stomach tissue, (iii) lost its gastroprotective activity following pretreatment with N-omega-nitro-L-arginine methyl ester (L-NAME; NO blocker) or carbenoxolone (CBXN; NP-SH blocker), (iv) exerted antioxidant activity against various in vitro oxidation assays, and (v) showed moderate in vitro anti-inflammatory activity via the LOX-modulated pathway. In conclusion, EAMM exerts a remarkable NO/NP-SH-dependent gastroprotective effect that is attributed to its antisecretory and antioxidant activities, ability to stimulate the gastric mucus production and endogenous antioxidant system, and synergistic action of several gastroprotective-induced flavonoids.